Die Begabungsforschung von William Stern Eine Einführung mit Quellentexten und unveröffentlichten Originaltexten - Heinemann, Rebecca (Verlag Julius Klinkhardt, 2023)
This volume offers an introduction to the research on giftedness by the philosopher and psychologist William Stern (1871-1938), the doyen and most exposed representative of empirical research on giftedness in Germany. Selected source texts and previously unpublished original texts provide a well-founded insight into his thinking and commitment to educational policy. The author's introductory texts introduce the main content, explain central aspects of Stern's research on giftedness and shed light on biographical, scientific-historical, educational and socio-political contexts. Excerpts from the diaries in which Clara and William Stern recorded observations of their children's development are also presented and evaluated for the first time in terms of their significance for giftedness research and support.